Transmission of environmentally responsible behavior between tourist destination employees and tourists: The role of moral elevation and environmental knowledge - Ye, Weijiao; Li, Ziqiang; Xu, Yuyan (Frontiers in Psychology, 2022)
Tourists’ environmental misconduct is the primary reason for the environmental destruction that tourist sites experience; nevertheless, their environmentally responsible behavior is also a major push for the improvement of the environment. The main goal of this study is to induce tourists to adopt proactive environmental responsibility behaviors. We chose moral elevation as a mediating variable to investigate the mechanism of transferring environmentally responsible behavior from employees to tourists. Furthermore, we investigate the moderating effect of environmental knowledge on the environmentally responsible behavior of employees and the moral elevation of tourists. Using a questionnaire survey method, we collected 455 questionnaires in Fujian Province, China, and empirically evaluated these surveys using multiple linear regression. The findings of this study indicate employees’ environmentally responsible behavior (E-ERB) in tourist destinations has a positive impact on tourists’ environmentally responsible behavior (T-ERB). In the mediating variable of moral elevation, the correlation between E-ERB and T-ERB was mediated by elevating emotions and views of humanity. And desire to be a better person did not play a mediating role in the relationship between E-ERB and T-ERB. Additionally, environmental knowledge moderates the transmission process of the impact of employees’ environmentally responsible behavior on tourists’ environmentally responsible behavior via elevating emotions. With high environmental knowledge, the transmission process of the impact of employees’ environmentally responsible behavior of the tourist destination on tourists’ environmentally responsible behavior via elevating emotions will be enhanced. We expect that our research will inspire additional research into the mechanisms underpinning the transmission of employee behavior to tourist behavior.